How/if the Future Changes the Professional Field of Social Work? - Adomaitytė-Subačienė, Ieva; Martinaityte, Guoda (Socialinė teorija, empirija, politika ir praktika, 2022)
The authors aim to discuss the changes in the professional field of social work, the future scenarios and the role of social work in the future society, and to present the views of social workers themselves on the future and the expected changes. The authors provide an overview of the trends in the development of social work profesion and outline the important changes in the professional field based on litearture review. The paper presents a quantitative survey of social workers in Lithuania, which aimed to uncover their attitudes towards new developments, the impact of technology and social innovation, and the future competences of social work. The results of the study reveal that employees see changes in the field of social work, but that these changes are marginal. Not seeing change and a negative public perception of social work are also associated with a willingness to move to another field of work. Leadership and professionalism of managers and more cohesive teamwork would encourage staff to stay. The study did not show that working for any institution (municipal, governmental, non-governmental, etc.) determines social workers‘ attitudes. Social workers‘ attitudes and evaluations were more influenced by their demographics: place of residence, age, education, but even these correlations were rather weak. A large proportion of respondents were not familiar with the Sustainable Development Goals (SGD2030) or had only participated in a few sustainability initiatives, but the importance of innovations in social work practice was identified by 58% of respondents, compared to 72% of those aged between 18 and 35 years. When talking about the future competences of social work, the traditional micro-level competences of social work are highlighted: empathy, emotional intelligence, interpersonal communication and working with a group, less importance is attached to innovative, managerial or macro-level competences.